2022
DOI: 10.3390/s22020527
|View full text |Cite
|
Sign up to set email alerts
|

MEMS Accelerometer Noises Analysis Based on Triple Estimation Fractional Order Algorithm

Abstract: This paper is devoted to identifying parameters of fractional order noises with application to noises obtained from MEMS accelerometer. The analysis and parameters estimation will be based on the Triple Estimation algorithm, which can simultaneously estimate state, fractional order, and parameter estimates. The capability of the Triple Estimation algorithm to fractional noises estimation will be confirmed by the sets of numerical analyses for fractional constant and variable order systems with Gaussian noise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Motivated by the study of Macias et al [24], where it was shown that the accelerometer's noise of MPU9250 contains the fractional order behaviour, we decided to make a noise analysis of its three-axes gyroscope. We utilise the TEA with various approximation lengths during the estimation process.…”
Section: Identification and Analysis Of Mems Gyroscope's Noisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the study of Macias et al [24], where it was shown that the accelerometer's noise of MPU9250 contains the fractional order behaviour, we decided to make a noise analysis of its three-axes gyroscope. We utilise the TEA with various approximation lengths during the estimation process.…”
Section: Identification and Analysis Of Mems Gyroscope's Noisesmentioning
confidence: 99%
“…In the study of Sierociuk and Macias [23], the triple estimation algorithm (TEA) for state vector, order and system parameters' estimation was proposed and described in detail. In the study of Macias et al [24], a triple estimation algorithm was used to carry out identification of fractional order noise in MEMS accelerometer measurements. In the practical application of the triple estimation algorithm, it was found that the algorithm requires quite a high numerical power.…”
Section: Introductionmentioning
confidence: 99%
“…Microelectromechanical system (MEMS) accelerometers are the crucial inertial sensors that find extensive applications in fields such as inertial navigation [ 1 , 2 , 3 , 4 ], vibration measurement [ 5 , 6 , 7 ], medical diagnosis [ 8 , 9 , 10 ], health monitoring [ 11 , 12 , 13 ], and disaster warning [ 14 , 15 , 16 ]. Presently, there is a growing demand for MEMS accelerometers with small sizes, high sensitivity, and superior stability [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The issue is illustrated, for example, by publications analyzing transversely oscillating MEMS viscometers [ 45 ] or fractional-order arch MEMS resonators [ 46 , 47 ]. A number of papers focus on advanced control techniques that help to improve the stability and performance of fractional-order MEMS [ 45 , 46 , 47 , 48 , 49 ], which are implemented using the sliding mode or fractional-order controllers. Such units can then exhibit complex fractional-order dynamics.…”
Section: Introductionmentioning
confidence: 99%